Immunochemical Investigation of the Serum Proteins in Chick Embryos - Peetoom, F.; Kraijenhoff Sloot, W. J. A. TH; Woerdeman, M. W. (Development (Cambridge), 1963)
The use of specific antisera against different embryonic antigens to detect a correlation between morphological and immunochemical differentiation in ontogenesis has proved to be a valuable technique. In a study of the appearance of lens proteins in chick embryos, using various antisera and agar precipitation methods, we observed the development of precipitation lines which did not correspond to specific lens proteins. These lines were encountered in the Ouchterlony and immunoelectrophoretic pictures obtained with young (up to 120 hr.) embryo or lens extracts when these were tested with antiserum to 24-hr, embryo extract or to adult chick serum. However, this type of precipitation band was never found when antiserum against adult chick lens was used. Some of our experimental results which clarify the nature of these precipitation reactions are summarized below. Full details of these experiments are the subject of another publication.